2022
DOI: 10.1007/s00217-022-04093-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alginate-based coating charged with hydroxyapatite and quercetin on colour, firmness, sugars and volatile compounds of fresh cut papaya during cold storage

Abstract: Active alginate-based coatings with quercetin glycoside and complexes of hydroxyapatite/quercetin-glycoside were used to study the shelf life of fresh cut papaya stored at 6 °C. Hydroxyapatite was used as a carrier for the release of the bioactive compound. The parameters considered affecting the quality of the fruit during storage were weight loss, color, texture, sugars and volatile compounds. Active coatings with hydroxyapatite and quercetin glycoside proved a higher capacity to slow down the degradation ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The luminosity values (L*) decreased over time for all treatments, indicating fruit ripening [66], with the exception of the group with encapsulated spearmint essential oils (CWN-MEO:β-CD), which showed higher values compared to the first day. The chroma (C * ) values of all groups also decreased, especially after the 5th day of storage, due to oxidative phenomena and the synthesis of papaya pigments such as carotene, lycopene, and anthocyanins during storage [67]. At the end of 15 days, the h • values of all treatments also decreased; as papaya matures, its color changes from greenish to yellowish due to chlorophyll degradation and carotenoid biosynthesis [68].…”
Section: Physicochemical Parameters Of Papayasmentioning
confidence: 96%
“…The luminosity values (L*) decreased over time for all treatments, indicating fruit ripening [66], with the exception of the group with encapsulated spearmint essential oils (CWN-MEO:β-CD), which showed higher values compared to the first day. The chroma (C * ) values of all groups also decreased, especially after the 5th day of storage, due to oxidative phenomena and the synthesis of papaya pigments such as carotene, lycopene, and anthocyanins during storage [67]. At the end of 15 days, the h • values of all treatments also decreased; as papaya matures, its color changes from greenish to yellowish due to chlorophyll degradation and carotenoid biosynthesis [68].…”
Section: Physicochemical Parameters Of Papayasmentioning
confidence: 96%
“…Thereafter, during longer storage periods, TSS decreased in both coated and uncoated guavas, which could be associated with the fact that glucose is the primary substrate of producing the energy required in the fruit metabolism . An earlier study also reported that the decrease in glucose content during later stages of storage might be due to the preference of microorganisms to use glucose as the primary substrate for the fermentation pathway . During 3 days of storage, no significant differences in the ripening index were observed among the uncoated and coated guavas.…”
Section: Resultsmentioning
confidence: 79%
“…50 An earlier study also reported that the decrease in glucose content during later stages of storage might be due to the preference of microorganisms to use glucose as the primary substrate for the fermentation pathway. 51 During 3 days of storage, no significant differences in the ripening index were observed among the uncoated and coated guavas. However, during 6 days of storage, the ripening index of the uncoated guavas rapidly increased from 30.9 to 36.4, whereas the AX-SAC-, AX-SAS-, and carnauba wax (1−4%)-coated guavas notably maintained the ripening index in the ranges of 30.4−31.1, 33.0−34.6, and 31.6−32.1, respectively (Figure 3C), indicating that these coatings helped to keep the balance of sugars and acids in the guava fruit, therefore delaying the ripening process.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…A higher amount of oxygen in fresh-cut papaya promotes the activation of PPO enzymes, increasing browning development and decreasing the bioactive compounds. Furthermore, essential oils can inhibit PPO activity, as Eissa et al [65] demonstrated in apple juice, where lemon grass oil extract showed inhibition of 92%. Regarding using nanostructures to decrease PPO activity, it has been found that in fresh-cut 'Red Delicious' apples treated with α-tocopherol nanocapsules, PPO enzyme activity was delayed compared to the CaCl 2 treatment [76].…”
Section: Ppo Activity Of Fresh-cut Papaya Treated With Nanoparticlesmentioning
confidence: 92%
“…The decrease in a* value in the control papaya (Figure 5) is attributed to the oxidation of carotenoids that give pigmentation to the fruit due to the absence of barriers that can interfere with oxygen distribution within the papaya tissues [65]. Papayas treated with NC C/EC and NC C/PCL did not differ significantly from the control.…”
Section: Changes In the Color Of Fresh-cut Papaya Treated With Nanosy...mentioning
confidence: 95%